The Synergistic Effect of Two Kinds of Insecticide in Water Flea Daphnia pulex (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study aimed to investigate synergistic effect of two kind of insecticide colti 5 and cypermethrin as a mixture pesticide in a volume ratio (1:1) on D. pulex individuals by using different concentrations (0.002, 0.0002, 0.00002) mg/l from it. Which the results appeared that percentage of mortality for D. pulex individuals was (80, 66, 30) % with LC50 (0.00015) mg/l after 24 hours from exposure to different concentration respectively. While the percentage of mortality for D. pulex individuals was (95, 80, 60) % with also LC50 (0.00015) mg/l after 72 hours from exposure to different concentration respectively. The results observation showed that the activity, size and egg sacs were different among the concentration that used compared to control. The results showed a significant difference in level of probability (0.05), and a positive correlation coefficient between percentage of mortalities and concentrations.